Disruptive mood dysregulation disorder, parental stress, and attachment styles - Marit Coldevin; Marit Coldevin; Astrid Brænden; Pål Zeiner; Pål Zeiner; Anne-Siri Øyen; Annika Melinder; Jan E. Stubberud (Frontiers in Child and Adolescent Psychiatry)
Disruptive mood dysregulation disorder (DMDD) is a relatively new diagnostic entity concerning children with chronic irritability and severe anger outbursts. Currently, there is limited knowledge about the parental factors associated with the disorder. The aim of this study was to compare stress levels and attachment styles in parents of children with DMDD with those of parents of children with other diagnoses. Our sample consisted of 218 children (6–12 years, Mage = 9.68 years) referred to child mental health outpatient clinics. Clinicians used a standardized semi-structured diagnostic interview to identify diagnoses. Parental stress levels and attachment styles were assessed using parent reports. We found that parents of children with DMDD experience significantly higher levels of parenting stress related to factors in the child than parents of children with other diagnoses. Furthermore, parents of children with DMDD show a higher association with insecure adult attachment styles than parents of children without DMDD. Finally, an adult preoccupied-ambivalent attachment style explains the variability in parental stress in the DMDD group to a large degree. We discuss how parental stress and an insecure attachment style can be associated with negative parenting practices. An implication from this study could be that treatment results might be improved by involving parents more in treatment programs for children with DMDD.